Predictors of Success in Horizontal Strabismus Surgery: Insights from a Prospective Study - Aurellia Valmai Tjujitno; Reni Prastyani; Joni Susanto; Rozalina Loebis; Luki Indriaswati; Lely Retno Wulandari (Juxta: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga)
Introduction: Strabismus is an eye disorder characterized by misalignment of the eyes, which can occur in individuals of any age. This study explored the surgical outcomes of horizontal strabismus correction in patients, aiming to provide insights into the factors influencing success.